1986
DOI: 10.1083/jcb.102.3.1099
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies distinguish titins from heart and skeletal muscle.

Abstract: Abstract. Murine monoclonal antibodies specific for titin have been elicited using a chicken heart muscle residue as antigen. The three antibodies T 1, T3, and T4 recognize both bands of the titin doublet in immunoblot analysis on polypeptides from chicken breast muscle. In contrast, on chicken cardiac myofibrils two of the antibodies (T 1, T4) react only with the upper band of the doublet indicating immunological differences between heart and skeletal muscle titin. This difference is even more pronounced for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 29 publications
3
38
0
Order By: Relevance
“…In addition, flexible, string-like structures morphologically similar to isolated titin were found located at the ends and alongside isolated native thick filaments [85,86]. Binding of anti-titin antibodies confirmed that these structures were titin filaments [9,25].…”
Section: B Antibody Studiesmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, flexible, string-like structures morphologically similar to isolated titin were found located at the ends and alongside isolated native thick filaments [85,86]. Binding of anti-titin antibodies confirmed that these structures were titin filaments [9,25].…”
Section: B Antibody Studiesmentioning
confidence: 92%
“…On the basis of variations in electrophoretic mobility [1,11,12,26,32,49,89,95, 100] and antibody reactivity [25], several investigators have demonstrated that different striated muscles of an animal can contain different isoforms of titin. Developmental changes in titin isoforms have also been documented [16,107].…”
Section: Dependence Of Passive Tension On Titin Isoformsmentioning
confidence: 99%
“…Electro° phoresis was performed on linear polyacrylamide gradient gels (2-12% acrylamide; 0.5% crosslinker) in the standard buffer system but omitting a stacking gel. Immunoblotting using hybridoma supernatants was as described [7]. Indirect immunofluorescence microscopy on frozen muscle sections was performed after acetone fixation by standard procedures using the hybridoma supernatants and FITC-labeled sheep anti-mouse antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…After digestion with restriction enzymes the samples of genomic DNA were electrophoresed on 0.8% agarose, blotted and hybridized to 32p-labeled probes as in [9]. The probes used were kindly provided by Dr P. Pearson (754) [7]). (d-h) Nebulin: (d) normal human skeletal muscle, Nb6, (e) case I, Nb4, (f) case I, Nbl, (g) case Ill, Nb4, (h) case III, Nbl (cross-section).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation